Trends in the burden of urolithiasis in China: an analysis from the global burden of disease study 2021 - Lin, Yangyang; Lin, Qing-cheng; Zhou, Qing-ying; Xu, Nai-fen; Zheng, Ding-qin; Wang, Xin-jun; Xu, Ran (Frontiers in Surgery, 2025)
BackgroundUrolithiasis is a common disease of the urinary tract, the global prevalence of which is increasing year by year and which, due to its high rate of recurrence and complications, represents a major burden on the quality of life of patients and on the global public health system. As the most populous country in the world, the epidemiology of urolithiasis in China is of great importance. However, the current systematic epidemiological assessment of urolithiasis in China is relatively limited. Therefore, this study used the GBD 2021 database to systematically assess the disease burden of urolithiasis in China to provide a basis for policy formulation.MethodsThis study analysed the disease burden of urolithiasis in China between 1992 and 2021, including the number of prevalence cases, prevalence rate and age-standardised prevalence rate, using data from the GBD 2021 database. Joinpoint regression models were used to identify changes in the annual trends of urolithiasis, using annual percent change and average annual percent change for description. Age-period-cohort and Bayesian age-period-cohort models were used to assess time trends in urolithiasis burden and to predict trends over the next 15 years, respectively.ResultThe age-standardised prevalence rate of urolithiasis in China has decreased from 96.23 per 100,000 in 1992 to 50.78 per 100,000 in 2021 for males and from 34.44 per 100,000 in 1992 to 22.04 per 100,000 in 2021 for females. While the number of men with the disease has declined slightly, the number of women with the disease has increased. The Joinpoint regression model showed that the age-standardised prevalence rate showed a consistent downward trend in both males and females, and that the periods in which the decline was most pronounced were very similar. The age-period-cohort model also confirmed that the period and cohort effects of urolithiasis showed a decreasing trend from year to year. In addition, the age effect suggested that the risk of urolithiasis tended to increase and then decrease with age, and that the risk was highest in the 55–59 age group. Finally, the Bayesian age-period-cohort prediction model showed that the age-standardised prevalence rate of urolithiasis in both males and females would show a slowly increasing trend over the next 15 years.ConclusionIn this study, we analysed the trend of the disease burden of urolithiasis in China during 1992–2021 by GBD 2021. The results showed that the burden of urolithiasis was significantly higher in males than in females. Furthermore, although the burden of urolithiasis has gradually improved in both men and women over the past 30 years, the BAPC prediction model suggests that the burden of urolithiasis is likely to increase in the next 15 years in both sexes. Therefore, prevention, early screening and treatment of urolithiasis in high-risk groups need to be strengthened to respond effectively to a possible future increase in burden.